SOCIAL CAPITAL AND POLITENESS STRATEGIES IN FOSTERING ETHNIC RELATIONS IN MALAYSIA AND PHILIPPINES - Dumanig, Francisco Perlas (Jurnal Ilmiah Peuradeun, 2014)
Social capital helps in developing relationships among people in a community or from one community to the other. The concept of social capital focuses on social relationships or individual relationship which is an important tool in building a united and progressive society. It goes without saying that in a multi-ethnic and multilingual society, social capital is necessary to help foster unity and harmony among various ethnic groups. However, such socialization and sharing of knowledge can be obstructed in multi-ethnic societies by social barriers in the form of negative preconceptions towards other ethnic groups. Stereotyping is the result of distancing due to prejudice, which is usually the result of ignorance of the values and culture of other groups. The similarities of the cultural and social values among the Malays, Chinese and Indians for instance, the use of address terms, non-verbal signs and discourse norms in interaction as politeness strategies within their ethnic groups or across the major ethnic groups foster better and harmonious relationships. Similarly, in the Philippines different ethnic groups from the various regions of the country are able to share the same culture and values when interacting with one another.